Age-associated decrease in global DNA methylation in patients with major depression - Tseng PT (Dove Medical Press, 2014)
Ping-Tao Tseng,1,2,* Pao-Yen Lin,1,3,* Yu Lee,1 Chi-Fa Hung,1 For-Wey Lung,4,5 Cheng-Sheng Chen,6,7 Mian-Yoon Chong1 1Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 2Department of Psychiatry, Tsyr-Huey Mental Hospital, Kaohsiung Jen-Ai’s Home, Taiwan; 3Center for Translational Research in Biomedical Sciences, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, Taiwan; 4Taipei City Psychiatric Center, Taipei City Hospital, Taipei, Taiwan; 5Graduate Institute of Medical Science, National Defense Medical Center, Taipei, Taiwan; 6Department of Psychiatry, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 7Department of Psychiatry, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan *These authors contributed equally to this work Background: Evidence has supported a role of DNA methylation in the pathophysiology of mood disorders. The purpose of the current study is to examine 5-methylcytosine (5-mc) and 5-hydroxymethylcytosine (5-hmc) levels in patients with major depressive disorder (MDD) at different disease states.Methods: Forty-nine patients with MDD and 25 healthy control subjects were included. The severity in the disease was assessed by using the 17-item Hamilton Rating Scale of Depression (HAM-D) (HAM-D ≥19 for severe MDD and HAM-D ≤7 for remitted MDD). The 5-mc and 5-hmc levels in leukocyte DNA were measured using an enzyme-linked immunosorbent assay-based method.Results: We found a significant decrease in 5-hmc and trends of decreasing 5-mc levels in patients with severe MDD compared to healthy controls (P=0.059 for 5-mc and P=0.013 for 5-hmc). The decrease in the level exists only in the older age group (P=0.035 for 5-mc and P=0.002 for 5-hmc) but not in the younger age group (P=0.077 for 5-mc and P=0.620 for 5-hmc). In addition, the 5-mc level was found to be inversely correlated with disease severity (P=0.011).Conclusion: Our results support a decrease in global DNA methylation associated with age in patients with severe depression. Further studies are needed to clarify the role of the methylation level as a disease marker of depression and whether antidepressant treatment changes the methylation profiles. Keywords: 5-methylcytosine, 5-hydroxymethylcytosine, antidepressant, mood disorder, gene modification, epigenetic